Aborsi: Antara Norma dan Fakta Dalam Kehidupan Sosial - Adekusuma, Juliadi (Musawa Jurnal Studi Gender dan Islam, 2003)
In this article, Juliadi Adekusuma puts forward data on abortion from around the world and from Indonesia. This data shows us that not all abortions are done by women without partners, and in fact the majority of abortions in Indonesia involve married women. This article also points out that the number of unsafe abortions is very high, and 13% of these result in the death of the mother.